Syncope, Fear of Falling and Quality of Life Among Older Adults: Findings From the Irish Longitudinal Study on Aging (TILDA) - McCarthy, Kevin; Ward, Mark; Romero Ortuño, Román; Kenny, Rose Anne (Frontiers in Cardiovascular Medicine, 2020)
Objective: Syncope is a prevalent condition that has a marked impact on quality of life. We examined the association between syncope and quality of life (QoL) and whether this association was explained by fear of falling (FoF). Methods: We examined data from Wave 3 of The Irish Longitudinal Study on Ageing (TILDA), of adults aged ≥50 years (n=4946) who were asked to report syncope and who completed the CASP-12 QoL instrument. Analyses were stratified by age and gender. Results: Over 20% of participants reported having a previous syncopal episode, while 8% reported a faint, blackout or unexplained fall in the last year. QoL scores decreased as the burden of syncope increased: linear regression models adjusted for covariates showed that those having had two or more syncopal episodes in the last year reported a significantly lower CASP-12 score compared to those with none (p=0.011). FoF partially mediated the association between syncope and QoL, particularly among younger participants. Conclusions: Syncope is a common condition among older adults that has a deleterious effect on QoL, with ≥2 recent syncopal episodes having a particularly adverse impact on QoL. FoF is a potential pathway which may both explain this association and allow therapeutic interventions by health practitioners.